Applying emerging core competencies to extension training courses for local food system practitioners - Hannah Dankbar; Courtney Long; Dara Bloom; Kaley Hohenshell; Emma Brinkmeyer; Bre Miller (Journal of Agriculture, Food Systems, and Community Development, 2023)
In 2019, a national group of local food system educators and practitioners identified over 140 foundational core competencies critical to local food system development work and began to identify existing educational resources related to these competencies. This process resulted in a new aggregated resource: the Local Food System Practitioner and Educational Resource Database. Included in this database is a core competency matrix that distinguishes three levels of learning for each competency so that practitioners can identify learning opportunities most closely tailored to their educational needs. It also serves as a framework and competency matrix for educators to use to help assess and communicate the learning outcomes of their curricula. This framework is the overall concept for understanding the competencies, and the matrix is the tool developed to assess and evaluate the level at which an educational resource teaches a competency. In this article we apply the newly create core competency matrix to two existing local food system development courses. We share lessons learned from applying the matrix and insights gained from comparing two introductory level courses. We conclude with recommendations for improving the resource database and matrix to a more user-friendly model for educators and local food system practitioners.